2011
DOI: 10.1089/scd.2011.0074
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Application of Intravenous Autologous Bone Marrow Infusion in Patients with Alcoholic Liver Cirrhosis

Abstract: The present study was conducted to evaluate the application and efficacy of autologous bone marrow infusion (ABMi) for improvement of liver function in patients with alcoholic liver cirrhosis (ALC). Five subjects and 5 control patients with ALC who had abstained from alcohol intake for 24 weeks before the study were enrolled. Autologous bone marrow cells were washed and injected intravenously, and the changes in serum liver function parameters, and the level of the type IV collagen 7S domain as a marker of fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…Recently, autologous BMC transplantation (a technique known as autologous BMC infusion therapy) has been applied for patients with liver cirrhosis and is reported to improve the serum levels of albumin and total protein, leading to an improvement of the Child-Pugh score (22). We have also applied this autologous BMC infusion therapy for patients with alcoholic cirrhosis, resulting in successful improvement of liver function (18).…”
mentioning
confidence: 99%
“…Recently, autologous BMC transplantation (a technique known as autologous BMC infusion therapy) has been applied for patients with liver cirrhosis and is reported to improve the serum levels of albumin and total protein, leading to an improvement of the Child-Pugh score (22). We have also applied this autologous BMC infusion therapy for patients with alcoholic cirrhosis, resulting in successful improvement of liver function (18).…”
mentioning
confidence: 99%
“…Studies have shown that six-months after an intravenous injection of cultured BMSCs, patients' liver function indexes, pathological results of hepatic tissue and color Doppler ultrasound were improved, indicating the safety and effectiveness of BMSCs for treating cirrhosis (Mohamadnejad et al, 2007). Several additional reports have shown successful BMSC treatment of patients with hepatic fibrosis (Terai et al, 2006;Kim et al, 2010;Amer et al, 2011;Saito et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While there is no initial evidence of impaired immune response during the early stages of alcoholic liver cirrhosis [6], the immune response may be reduced later as the disease progresses, especially in the advanced stages of liver failure [7]. As a result of this disease profile, HSCs are eliminated by the active immune cells during the treatment of early-stage alcoholic liver cirrhosis, and accompanied by exacerbating the progression of hepatic fibrosis [8]. A previous study shows that two among eight patients receiving HSCs for the treatment of alcoholic liver cirrhosis, there was one case of diabetes (an autoimmune disease) with graft-versus-host disease, and another patient developed deterioration of liver function with the hemorrhage of the upper digestive tract [9].…”
Section: Introductionmentioning
confidence: 99%